Prognostic Value of Microvascular Density in Dukes A and B (T1–T4, N0, M0) Colorectal Carcinomas. (4th November 2009) - Uribarrena A, Rafael; Ortego, Javier; Fuentes, Javier; Raventós, Nuria; Parra, Pilar; Uribarrena E, Rafael
Abstract : Background . Aproximatelly 30% of patients operated on for colorectal cancer (CRC), with an expectedly favourable prognosis (Dukes A-B/T1–T4, N0, M0) suffer recurrence and/or die. Method . In order to determine if tumor microvascular density (MVD) is a prognostic factor in CRC, samples from tumors of 104 Dukes A-B CRC patients were retrospectively studied. Immunohistochemistry was performed for anti-CD34 antibody to visualize tumor vascularisation. MVD was expressed as the total number of vessels and as the percentage of microvascular area. We calculated MVD with a morphometry program and performed descriptive, bivariate, and survival statistics. Results . The mean number of vessels was 37.37/200x field, and the mean vascular area was the 3.972%. 30% of the patients with< 37 vessels/field, and 21% of the patients with> 37 vessels/field, experienced recurrence/death. The 35% of patients with< 4 % of vascular area died following recurrence, compared with 14% of patients with ≥4% of vascular area. These differences in % of vascular area were statistically significant. Conclusion . MVD expressed as the total number of vessels had no a statistically significant influence on the evolution of CRC. However, neoplasias with a greater % of vascular were associated to a better outcome.